Antiproliferative activity of cardenolide glycosides from Asclepias subulata - Rascón-Valenzuela, L.; Velázquez, C.; Garibay-Escobar, A.; Medina-Juárez, L. A.; Vilegas, Wagner [UNESP]; Robles-Zepeda, R. E. (Elsevier B. V., 2015)
Asclepias subulata Decne. is a shrub occurring in Sonora-Arizona desert (Mexico-USA). The ethnic groups, Seris and Pimas, use this plant for the treatment of sore eyes, gastrointestinal disorders and cancer. To isolate the compounds responsible for antiproliferative activity of the methanol extract of A. subulata. A bioguided fractionation of methanol extract of A. subulata was performed using MTT assay to measure the antiproliferative activity of different compounds on three human cancer cell lines (A549, LS 180 and PC-3), one murine cancer cell line (RAW 264.7) and one human normal cell line (ARPE-19). The methanol extract was partitioned with hexane, ethyl acetate and ethanol. The active fractions, ethanol and residual, were fractioned by silica-column chromatography and active sub-fractions were separated using HPLC. The chemical structures of isolated compounds were elucidated with different chemical and spectroscopic methods. A new cardenolide glycoside, 12, 16-dihydroxycalotropin, and three known, calotropin, corotoxigenin 3-O-glucopyranoside and desglucouzarin, were isolated of active sub-fractions. All isolated compounds showed a strong antiproliferative activity in human cancer cells. Calotropin was the more active with IC50 values of 0.0013, 0.06 and 0.41 µM on A549, LS 180 and PC-3 cell lines, respectively; while 12, 16-dihydroxycalotropin reached values of 2.48, 5.62 and 11.70 µM, on the same cells; corotoxigenin 3-O-glucopyranoside had IC50 of 2.64, 3.15 and 6.62 µM and desglucouzarin showed values of 0.90, 6.57 and 6.62, µM. Doxorubicin, positive control, showed IC50 values of 1.78, 6.99 and 3.18 µM, respectively. The isolated compounds had a weak effect on murine cancer cells and human normal cells, exhibiting selectivity to human cancer cells. In this study, we found that 12, 16-dihydroxicalotropin, calotropin, corotoxigenin 3-O-glucopyranoside and desglucouzarin are responsible of antiproliferative properties of A. subulata, and that these compounds are highly selective to human cancer cells. Further studies are needed in order to establish the action mechanisms of the isolated compounds.
Keywords: Antiproliferative activity; Asclepias subulata; Cardenolide glycosides